If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -10 + -1x + -4 = 3 Reorder the terms: -10 + -4 + 12x + -1x = 3 Combine like terms: -10 + -4 = -14 -14 + 12x + -1x = 3 Combine like terms: 12x + -1x = 11x -14 + 11x = 3 Solving -14 + 11x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 11x = 3 + 14 Combine like terms: -14 + 14 = 0 0 + 11x = 3 + 14 11x = 3 + 14 Combine like terms: 3 + 14 = 17 11x = 17 Divide each side by '11'. x = 1.545454545 Simplifying x = 1.545454545
| 7[x-(4x-7)]=7-6x | | 3xy-12x+7y-28= | | -9k-14=13 | | x^2*29x=0 | | x-3=x-12 | | 3(2x-5)=12x | | 12=-9+3j | | 25-Y=7 | | (x-1)+26=-4x | | (2x-5)(2x-5)(2x-5)= | | 16x^2+16x+480=h(x) | | 15x^2y^2-7xy^2-2y^2= | | 16x^2+16x+480=0 | | -4n+5=21 | | A-14=-4 | | 10(2f-3)=4f-8 | | 9(3.333)+y=30 | | 6x-14=6x+10 | | 9x-24=93 | | 20x+20y=200 | | 5n-n-2=11 | | 155=x+(x-5)+4(x-5) | | 3(-2-3x)= | | -3(8x+11)=6(-4-13) | | 4x+9=x+2x-3 | | -53=7*x+13 | | 155=x+(x-5)+4x | | 9x-10y=-16 | | y=3x+21 | | 12x^2-8x=8 | | 3(a+2)=14-2(3-2a) | | 9x+8y=-13 |